2023
DOI: 10.1177/10711007231165308
|View full text |Cite
|
Sign up to set email alerts
|

Split Transfer of the Tibialis Anterior Tendon Combined With Calcaneocuboid Fusion vs Split Transfer of the Tibialis Anterior Tendon Alone to Treat Equinovarus Foot Deformity in Children With Cerebral Palsy

Abstract: Background: The study aimed to compare the outcomes of combined calcaneocuboid arthrodesis and split anterior tibialis tendon transfer (SPLATT) procedure to isolated SPLATT surgery for the treatment of the spastic equinovarus deformity in children with cerebral palsy (CCP). Methods: Forty-one ambulatory CCP with 56 equinovarus feet, with positive flexor withdrawal reflex test results, were studied. The average age was 9.1 ± 3.2 years (range 3-22). Patients were assigned into 2 groups based on the surgical proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Equinovarus deformity is a common foot deformity that occurs in cerebral palsy which is due to a dynamic imbalance between the invertors and evertors leading gradually to a more fixed deformity. We read with interest the study by Bacaksız et al 1 on the role of calcaneocuboid fusion (CCF) along with split tibialis anterior tendon transfer (STATT) in such children. The authors concluded that addition of CCF to a STATT procedure generally resulted in better functional outcomes in comparison to isolated STATT procedure in a spastic equinovarus foot.…”
mentioning
confidence: 99%
“…Equinovarus deformity is a common foot deformity that occurs in cerebral palsy which is due to a dynamic imbalance between the invertors and evertors leading gradually to a more fixed deformity. We read with interest the study by Bacaksız et al 1 on the role of calcaneocuboid fusion (CCF) along with split tibialis anterior tendon transfer (STATT) in such children. The authors concluded that addition of CCF to a STATT procedure generally resulted in better functional outcomes in comparison to isolated STATT procedure in a spastic equinovarus foot.…”
mentioning
confidence: 99%